Security mechanisms in the global South: Asia, South America and Africa in comparison - Aguilar, Sérgio Luiz Cruz (My University, 2016)
The impact of the ‘Asian Century’ on global security politics is on the minds of international organizations and political decision makers. The Asian Development Bank (ADB) presented the Asian Century as the best perspective scenario on which economies can maintain their momentum for another 40 years and adapt to the shifting global economic and technological environment. ‘In this scenario, Asia’s GDP (at market exchange rates) increases from $17 trillion in 2010 to $174 trillion in 2050, or half of global GDP, similar to its share of the global population.'1.